CLASSIFYING GENOTYPIC, PHENOTYPIC VARIABILITY, BROAD SENSE HERITABILITY AND PRINCIPAL COMPONENTS OF SUGARCANE (ð˜šð˜¢ð˜¤ð˜¤ð˜©ð˜¢ð˜³ð˜¶ð˜® ð˜°ð˜§ð˜§ð˜ªð˜¤ð˜ªð˜¯ð˜¢ð˜³ð˜¶ð˜® L.) GENOTYPES FOR BETTER YIELD, QUALITY AND RESISTANCE AGAINST RED ROT - Ali, Bakatair; Tabasum, Saba; Nawaz, Sehar; Akhtar, Naeem; Kainat, Wardah (REVISTA DE AGRICULTURA, 2022)
Sugarcane is one of the important cash crops for Pakistan and it has been the primary source of sugar production. Sugarcane is used in our sugar mills and it’s by products are used in making cattle feed, soil manure etc. Present research experiment was conducted to assess the 32 genotypes of sugarcane collected from different farms for cane yield through yield contributing traits in natural field conditions. Traits like Cane height, cane girth, area of leaf, no. of internodes, internode length, no. of tillers, weight of cane, brix percentage and red rot disease incidence and severity were considered for evaluation of sugarcane germplasm. Result showed that most of the traits showed significance amount of variability between the genotypes with respect to the considered plant parameters. XT910 genotype showed the highest cane height while SPF-237 showed highest cane diameter. MSH-2415 showed the largest area of leaf as compare to other genotypes. XT236 showed the highest number of tillers per stool. Highest sucrose value is ultimate goal of breeders and US 133 showed highest sucrose value with brix percentage mean of 22. This variety performed very well overall. Sugarcane genotypes US-133,US-633,US-127,CPF-247,MSH-2415 were found excellent for sugar recovery while SPF-213 and SPF-237 were observed as resistance/tolerant against Red Rot. Furthermore, SPF-213, US-133, US-633 and US-127were found genetically diverse genotypes for different calculated traits and would be useful in sugarcane breeding program to enhance sugar recovery and Red rot resistance/tolerance in advanced sugarcane genotypes. With the help of this experiment study, we have isolated the SPF-213 variety of sugarcane which showed minimum incidence of Red rot disease. This variety has potential to perform well under Red rot susceptible environment.